Designing Affective Domain Evaluation Instrument for Basics Electrical Subject in Vocational High School - Ponto, Hantje; Jantje Tasiam, Fid; Wonggo, Djafar (International Journal of Engineering and Technology, 2018)
In general, in the learning process, teachers only perform the evaluation of the cognitive and psychomotor domains. So often affective areas less attention. Affective domains include feelings and emotions as well as the typical behavior of a person that impacts the learning process, because a person performing a learning activity is affected by a typical behavior. The objective of the research is to design the instrument of evaluation of the affective domain in the learning of Electrical Basics in Vocational High School (SMK). This instrument is required in order to know the students' affective behavior. Benefits of the research is to produce an instrument that can measure affective behavior as a reference for teachers to guide and direct the behavior of students in Basics Electrical learning activities so that students are directed to follow the learning process. The process of guidance and guidance of this behavior can continue until they plunge in the business and industry and socialize with the community. The research location is in North Sulawesi Province. The method used in this research is research and development.Â Â